2020
DOI: 10.1186/s13018-020-01638-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of knee injuries among male college students in Riyadh, Kingdom of Saudi Arabia

Abstract: Background: The knee is considered the most common injured joint between young sport participants. However, there is lack of proper prevalence estimation in our population. The purpose of this study was to identify the prevalence of knee injuries among male college students and to observe the demographic data associated with it. Our secondary objective was to evaluate the awareness and knowledge about these injuries. Methods: This is a cross-sectional study. A survey was distributed to collect the data among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
8
13
1
2
Order By: Relevance
“…ere were 66 cases (58.93%) suffered from MT, including 56 cases (50.00%) of LM and 10 cases (8.93%) of MM; there were 32 cases (28.57%) of edge tearing, including 30 cases (26.79%) of LM and 2 cases (1.79%) of MM; there were 8 cases (7.14%) of barrel-handle tearing, with all being LM; there were 8 cases of oblique laceration (7.14%), including 6 cases of LM (5.36%) and 2 cases of MM (1.79%); there were 12 cases of radiation tear (10.71%), including 8 cases of LM (7.14%) and 4 cases of MM (3.57%); there were 6 cases of horizontal tearing (5.36%), including 4 cases of LM (3.57%) and 2 cases of MM (1.79%); there were 16 cases of MC (14.29%), with all being LM; and there were 18 cases of MDI (16.07%), including 4 cases of LM (3.57%) and 14 cases of MM (12.50%). Such results were consistent with the findings of Almaawi et al [18], who selected 103 patients with TPF examined by MRI and found that the incidence of soft tissue injury was as high as 99%, and 91% of patients had LM injury. e incidences of MI in the Schatzker subtypes were 0%, 53.33% (24/45), 41.67% ( showing statistically remarkable differences (P 0.05); but the incidence of MT was 54.46% (61/112), which was much higher in contrast to that of MC.…”
Section: Discussionsupporting
confidence: 92%
“…ere were 66 cases (58.93%) suffered from MT, including 56 cases (50.00%) of LM and 10 cases (8.93%) of MM; there were 32 cases (28.57%) of edge tearing, including 30 cases (26.79%) of LM and 2 cases (1.79%) of MM; there were 8 cases (7.14%) of barrel-handle tearing, with all being LM; there were 8 cases of oblique laceration (7.14%), including 6 cases of LM (5.36%) and 2 cases of MM (1.79%); there were 12 cases of radiation tear (10.71%), including 8 cases of LM (7.14%) and 4 cases of MM (3.57%); there were 6 cases of horizontal tearing (5.36%), including 4 cases of LM (3.57%) and 2 cases of MM (1.79%); there were 16 cases of MC (14.29%), with all being LM; and there were 18 cases of MDI (16.07%), including 4 cases of LM (3.57%) and 14 cases of MM (12.50%). Such results were consistent with the findings of Almaawi et al [18], who selected 103 patients with TPF examined by MRI and found that the incidence of soft tissue injury was as high as 99%, and 91% of patients had LM injury. e incidences of MI in the Schatzker subtypes were 0%, 53.33% (24/45), 41.67% ( showing statistically remarkable differences (P 0.05); but the incidence of MT was 54.46% (61/112), which was much higher in contrast to that of MC.…”
Section: Discussionsupporting
confidence: 92%
“…Comparable rates have been reported in other studies carried out in Saudi Arabia (10.3%)[ 18 ] and India (13.5%). [ 20 ] However, higher rates were reported in studies carried out locally in Riyadh (23.2%)[ 21 ] and UK (31.8%). [ 22 ] Moreover, the prevalence rate reported in the current study falls within the worldwide prevalence ranging between 10 and 25% as documented by a systematic review published by Louw QA et al .…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the knee include bone, cartilage, and ligament injuries. There are many ligament injuries, and bone or cartilage injuries are generally combined with one or several ligament injuries [1,15].…”
Section: Mechanism and Characterization Of Knee Injurymentioning
confidence: 99%